Catalogação descritiva no século XXI: um estudo sobre o RDA - Corrêa, Rosa Maria Rodrigues [UNESP] (Universidade Estadual Paulista (Unesp), 2008)
Information and its transmission are essentials at the threshold of the XXI century Descriptive cataloging being an area of the Library Science is responsible for transmitting information existing inside of holdings of all types. This is made by building forms of representation and must follow the evolution of the needs of users. This affirmation worries specialists of the area. Standardization is indispensable in the representation of information and documents and it is also the aim of descriptive cataloging work; it is a grant for the exchange of bibliographic records. The worry increases as fast as the creation of new information available in different forms. The goal of this work is to analyze the state-of-the art of the standard “Resource Description and Access (RDA)” developed by the International Federation of Libraries Associations (IFLA) for catalogers and workers in bibliographic database. This work is founded in on-line bibliographic researches. The building of the historic of this work was based in the following factors: evolution of cataloging and its codes of rules; influence of technology in the communication media specifically in the exchange of bibliographic information; compatibility of concepts to reach an efficient communication between machine, cataloger and coded information to attend the user. This study of RDA was elaborated getting together the informational needs, the descriptive cataloging and the new standard, in order to understand its scope and if it is possible the international acceptance of it, as a form of bibliographic control as well as a way to enlarge the access and use of information available in the most different informational environments. Since RDA is a standard that is being developed, it may only be studied at the theoretical point of view. We verified that RDA is an effective standard since it links theory and practice.

A informação é essencial neste limiar do Século XXI, assim como sua transmissão. A catalogação descritiva, como área da Biblioteconomia responsável por transmitir as informações contidas em acervos de qualquer natureza, por meio da construção de formas de representação, deve acompanhar a evolução das necessidades dos usuários. Esta constatação preocupa especialistas da área. A padronização, na representação das informações e documentos é imprescindível e também o objeto de trabalho da catalogação descritiva como forma de garantia do intercâmbio de registros bibliográficos. A preocupação cresce com a rapidez com que as informações são geradas e disponibilizadas em diferentes formas. Este trabalho propõe-se a analisar o estado da arte do esquema Resource Description and Access (RDA) elaborado pela International Federation of Libraries Associations (IFLA), para uso de catalogadores e bases de dados bibliográficos. A análise baseia-se em pesquisas bibliográficas on-line. A evolução da catalogação e seus códigos de regras; a influência das tecnologias nos meios de comunicação, especificamente na troca de informações bibliográficas; a compatibilidade de conceitos visando a comunicação eficiente entre máquina, catalogador e informações codificadas para atendimento dos usuários foram utilizadas para a construção da parte histórica do trabalho. O estudo do RDA foi elaborado reunindo-se as necessidades informacionais, a catalogação descritiva e o novo esquema para compreender sua abrangência e a sua possível aceitação internacional, como uma forma de possibilitar o controle bibliográfico e ampliar o acesso e uso das informações disponíveis nos mais diversos ambientes informacionais. O RDA, por ser um esquema em fase de elaboração somente pode ser analisado do ponto de vista teórico. Nossa análise verificou que o RDA é um esquema eficaz, por aliar a teoria à prática.
Keywords: Catalogação descritiva; Códigos de catalogação; RDA; Resource Description and Access (RDA); Descriptive representation; Cataloguing codes; Paris principles